Incidence of left ventricular diastolic dysfunction in patients with subclinical hypothyroidism - Kapri, Vineet; R., Harshitha; Kumar, V. Shreyas (International Journal of Research in Medical Sciences, 2025)
Background: Subclinical hypothyroidism (SCH) is a common endocrine disorder categorized by increased serum thyroid-stimulating hormone (TSH) levels with normal free thyroxine (FT4) levels. The study determined the prevalence of LVDD in females aged 20 to 50 years with SCH and to explore the relationship between serum TSH levels and left ventricular diastolic dysfunction (LVDD). Methods: One hundred female participants aged 20 to 50 years with SCH were included in this study conducted between September 2014 to October 2015. All participants underwent 2D echocardiography to assess diastolic function. Data were collected on age, serum FT3, FT4, TSH levels, and echocardiographic parameters. Statistical analysis was achieved using SPSS. Results: The study found that 34% of the participants had LVDD. The prevalence of LVDD was significantly higher in the 36-50 age group (45.8%) compared to the 20-35 age group (23.1%). A considerable correlation was observed between elevated serum TSH levels (8-10 µU/l) and the prevalence of LVDD (47.1%) compared to lower TSH levels (5-7 µU/l) (22.2%). Echocardiographic findings showed significantly lower E/A ratios and increased left atrial volume indices in participants with LVDD (p<0.001). Conclusions: The study demonstrated a substantial incidence of LVDD among females with SCH, particularly in older participants and those with higher TSH levels. These findings suggest that advancing age and elevated TSH levels are important risk factors for LVDD in this population. Regular cardiac assessments and monitoring of thyroid function are recommended for females with SCH, especially those in older age groups or with elevated TSH levels, to prevent the progression to overt cardiovascular disease.